2006
DOI: 10.1371/journal.pbio.0040327
|View full text |Cite
|
Sign up to set email alerts
|

CDPKs CPK6 and CPK3 Function in ABA Regulation of Guard Cell S-Type Anion- and Ca2+- Permeable Channels and Stomatal Closure

Abstract: Abscisic acid (ABA) signal transduction has been proposed to utilize cytosolic Ca2+ in guard cell ion channel regulation. However, genetic mutants in Ca2+ sensors that impair guard cell or plant ion channel signaling responses have not been identified, and whether Ca2+-independent ABA signaling mechanisms suffice for a full response remains unclear. Calcium-dependent protein kinases (CDPKs) have been proposed to contribute to central signal transduction responses in plants. However, no Arabidopsis CDPK gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
597
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 540 publications
(639 citation statements)
references
References 105 publications
20
597
2
4
Order By: Relevance
“…However, due to the fact that both K + and Ca 2+ can permeate through the TPC1 channel it is still debated whether the phenotype observed is derived from altered K + fluxes or from TPC1-dependent Ca 2+ signaling. Given recent evidence for roles of CDPKs in transducing ABA regulation of anion and Ca 2+ channels at the GC plasma membrane [104], it is anticipated that new connections may also soon emerge between ABA, CDPKs and regulation of tonoplast transport. A possible link between extracellular Ca 2+ concentration and tonoplast transport is indicated by the recent observation that the generation of Ca 2þ cyt oscillation is regulated by external Ca 2+ concentration via an apoplastic Ca 2+ sensor (CAS)-mediated CAS-InsP 3 pathway in Arabidopsis [153].…”
Section: Vacuolar Ion Transporters: Properties and Regulationmentioning
confidence: 99%
“…However, due to the fact that both K + and Ca 2+ can permeate through the TPC1 channel it is still debated whether the phenotype observed is derived from altered K + fluxes or from TPC1-dependent Ca 2+ signaling. Given recent evidence for roles of CDPKs in transducing ABA regulation of anion and Ca 2+ channels at the GC plasma membrane [104], it is anticipated that new connections may also soon emerge between ABA, CDPKs and regulation of tonoplast transport. A possible link between extracellular Ca 2+ concentration and tonoplast transport is indicated by the recent observation that the generation of Ca 2þ cyt oscillation is regulated by external Ca 2+ concentration via an apoplastic Ca 2+ sensor (CAS)-mediated CAS-InsP 3 pathway in Arabidopsis [153].…”
Section: Vacuolar Ion Transporters: Properties and Regulationmentioning
confidence: 99%
“…4b-d). R-type anion currents 11 were activated as described 25,28 . Interestingly, no significant differences in Rtype anion currents between wild-type and slac1 guard cells were observed (Fig.…”
mentioning
confidence: 99%
“…Disruption of these two genes produced defects in ABA-and Ca 2+ -activation of S-type anion channel. Additionally, ROS (reactive oxygen species)-activation of I Ca -channel was also reduced in the cpk3 cpk6 mutant suggesting CPK3 and CPK6 might control downstream of ROS and Ca 2+ signaling steps in ABA signal transduction (Mori et al, 2006) (Fig. 2).…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 94%
“…CPK3 and CPK6 are the major CDPKs expressed in guard cells and regulate ABA induction of S-type anion channel and Ca 2+ -permeable channels (Mori et al, 2006). Single cell typebased guard cell microarray analyses identified that CPK3 and CPK6 expressions were mainly localized in guard cells.…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 99%
See 1 more Smart Citation